2002
DOI: 10.1172/jci15614
|View full text |Cite
|
Sign up to set email alerts
|

P311 induces a TGF-β1–independent, nonfibrogenic myofibroblast phenotype

Abstract: P311, also called PTZ17, was identified by suppressive subtraction hybridization as potentially involved in smooth muscle (SM) myogenesis. P311 is an 8-kDa protein with several PEST-like motifs found in neurons and muscle. P311 transfection into two fibroblast cell lines, NIH 3T3 and C3H10 T1/2, induced phenotypic changes consistent with myofibroblast transformation, including upregulation of SM α−actin and SM22, induction of FGF-2, VEGF, PDGF, and PDGF receptors, upregulation of integrins α3 and α5, and incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
44
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 54 publications
(111 reference statements)
3
44
0
Order By: Relevance
“…Furthermore, we found that all three TGFbs are fibrogenic and placed P311 as a stimulator of fibrosis acting immediately upstream of TGF-b1 to -b3. Because P311 expression is up-regulated or down-regulated by hormones, 52 retinoic acid, 53 growth factors, 54 and mechanical tension, 4 and because P311 has proven to be decreased in muscular atrophy 55,56 and pulmonary emphysema, 6 it is likely that in pathologic conditions with decreased P311 expression scar formation will be affected in ways similar to those presented in this study, leading thereby to a higher risk of dehiscence.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…Furthermore, we found that all three TGFbs are fibrogenic and placed P311 as a stimulator of fibrosis acting immediately upstream of TGF-b1 to -b3. Because P311 expression is up-regulated or down-regulated by hormones, 52 retinoic acid, 53 growth factors, 54 and mechanical tension, 4 and because P311 has proven to be decreased in muscular atrophy 55,56 and pulmonary emphysema, 6 it is likely that in pathologic conditions with decreased P311 expression scar formation will be affected in ways similar to those presented in this study, leading thereby to a higher risk of dehiscence.…”
Section: Discussionsupporting
confidence: 50%
“…Our previous data indicated that P311 stimulates TGF-b translation in vascular smooth muscle cells as well as in NIH 3T3 cells. 2,4 Therefore, as part of the present study we determined whether P311 also has a similar effect in keratinocytes and dermal fibroblasts. To this end, we transfected P311 into MFs, HFs, and HKs, which under normal conditions lack the protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, myofibroblast differentiation could also be generated independent of TGF-βs. For example, the plasmid containing the cDNA of a 8 kDa protein, P311, induced myofibroblast differentiation when transfected into fibroblasts [Pan et al, 2002].…”
mentioning
confidence: 99%
“…It can bind to TGF-β latency associated protein and stimulate the translation of TGF-β. In addition, P311 has proved to be of importance in the process of myofibroblast differentiation and fibrosis with functions of promoting embryonic development, wound healing, as well as nerve and lung regeneration, and so on (18)(19)(20)(21)(22). In our previous studies, we found that P311 might be involved in the pathogenesis of renal fibrosis by inhibiting the EMT process via the TGF-β1-Smad-ILK pathway in vitro (23).…”
Section: Introductionmentioning
confidence: 92%